Pedalando para sobreviver: o processo de uberização do trabalho e os entregadores ciclistas - Moura, Lívia Romero de (2021)
The current work scenario is marked by a process of loss of social rights, flexibility, instability and precariousness, leading to new forms of work. The Uber company is one of the most illustrative about this new capitalist facet, which, due to its strong representation, brought a new lexicon to the corporate world: the uberization of work. The global phenomenon deepens the process of job insecurity and causes a new category of workers to emerge, which is eminently precarious, but which takes on new shapes and reveals itself as another possibility of survival for thousands of workers in the country, that of cyclists. In face of this, the present work proposed to analyze with the cyclists delivery how the phenomenon of uberization constitutes reference in their work experience. Specifically, we seek to highlight the consequences of flexibilization and precariousness in the work trajectories of cyclist deliverers; understand the implications for labor temporality produced by the phenomenon of uberization; and to identify elements of the precariousness and flexibility of bicycle delivery work. The research, of qualitative character, used the semi-structured interview for the construction of the data, with focus on the work trajectory, and a research diary. As a proposal for analyzing the data built in the field, we favor Sociological Discourse Analysis. From our investigation, we perceived different angles of perception about bicycle delivery activities, ranging from the pains inherent to an eminently precarious occupation, to a look that, starting from a work trajectory, gives a certain positivity to the occupation, such as reference to a viable possibility of survival, especially for marginalized groups. In addition, we apprehend a spatio-temporal reconfiguration of the bicycle delivery activity, evidenced by an apparent dichotomy between fixed hours versus flexible hours, but which reveal themselves to be faces of the same process of precarious work. Regarding the spatial composition, we spoke from the perspective of a “no place” in the activity of cycle-deliverers by application and the implications of this condition. Finally, we are faced with the understanding of a “marginal look” that falls on the delivery worker and gives a judgmental look that constrains and drives a process of social exclusion. In addition to this symbolic violence, urban violence in the path of the delivery person, which thickens the condition of vulnerability and attacks not only the instruments of work, but also the life itself. There is also an ongoing corrosion project for the working class, enhanced bynew jobs per application. However, we see traces of class solidarity, sparks of resistance and organization of collective struggle.